Ghost in the machine. (Economist, 2009)
This article discusses the need for computer security measures that can distinguish between nuisances such as distributed denials of service errors and actual attempts at sabotage. When considering allegations that the North Koreans coordinated a cyberattack from an elite group of hackers, the article considers the possibility that any programmer could have originated such a disruption. Comments from the security firm Arbor Networks regarding the origins of the attack are noted.